Privatizing Infrastructure : Capital Market Pressures and Management Incentives - Irwin, Timothy (World Bank, Washington, DC, 2012)
The authors propose a number of privatization rules to ensure that management will improve after privatization. Governments should ensure that the privatized sector has several firms operating in industries that are local natural monopolies, so that if one operator goes bankrupt, another can readily take over. Governments should also permit concentrated ownership and foreign ownership, and profits should not be guaranteed through regulation.